PENGEMBANGAN KEWIRAUSAHAAN GULA SEMUT DI KECAMATAN WADASLINTANG KABUPATEN WONOSOBO - Akhmad Efendi; Sulistyani Budiningsih; Rahmi Hayati Putri (Universitas Muhammadiyah Purwokerto, 2017)
This research aims to find out the characteristics of (Brown Sugar) producers, the processing of water coconut sap until it is certified with Control Union, and the developmental strategies of brown sugar entrepreneurship in Wadaslintang Sub-district of Wonosobo. The data were collected through observation, interview, documentation and were analysed using qualitative descriptive technique. A qualitative approach was used to determine the characteristics of brown sugar producers in Wadaslintang Sub-district and to analyse the entrepreneurial condition of brown sugar farmers/producers. Developmental patterns of brown sugar entrepreneurship was analysed through SWOT technique (Strengths, Weaknesses, Opportunities, Threats). The research result indicated that: first, the characteristics of brown sugar producers in Wadaslintang Sub-district (including age, education level, and duration of running brown sugar entrepreneurship) belong to adequate category for developing brown sugar entrepreneurship. Second, brown sugar in Wadaslintang Sub-district is still processed traditionally. However, the production can get into the export market. Third, the developmental strategies of brown sugar entrepreneurship include expanding the target, maintaining and improving the quality of gula semut production, improving promotion to people and maintaining the good relation with the customers.